Survey of dermoscopy use by Taiwanese dermatologists - Kuo, Yi-Wen; Chang, Ying-Jui; Wang, Shu-Hui; Lu, Po-Hsuan; Su, Yung-Ling; Chu, Thomas Waitao; Chu, Gong-Yau (Zhonghua pi fu ke yi xue za zhi, 2015)
Abstract Background Dermoscopy is a useful technique for improving the diagnostic accuracy of various types of skin disorders. Although the technique has been widely adopted by European, Australian, and United States dermatologists, only limited information is available on the prevalence of dermoscopy use in Taiwan. Objectives We assessed the use and barriers to adoption of dermoscopy among Taiwanese dermatologists to determine the relationship between dermoscopy use and the characteristics of dermoscopy users. Methods A questionnaire of 20 items regarding demographic characteristics, dermoscopy training, and application was mailed to all dermatologists listed in the 2013 Taiwanese Dermatological Association registry. Results: Of the 950 mailed questionnaires, 202 were returned and 195 were identified to be eligible. Of the valid respondents, 51.8% used dermoscopy and 62.1% had attended courses for dermoscopy training. Dermoscopy use was significantly associated with women ( p  = 0.018), residents ( p  < 0.001), young age ( p  < 0.001), dermoscopy training ( p  < 0.001), and owning dermoscopy books ( p  < 0.001). The majority of dermoscopy users practiced in medical centers ( p  < 0.001) and were involved in resident teaching ( p  < 0.001). If more convenient programs for dermoscopy training were offered (68.1%), the price of a dermatoscope was lowered (64.9%), or free trials were offered by dermatoscope vendors (58.5%), dermoscopy nonusers might be willing to use this technique. Conclusion This is the first published survey about the application of dermoscopy in Taiwan. Despite a low response rate and potential selection bias, our study revealed that dermoscopy is increasingly being accepted by Taiwanese dermatologists in daily practice. In addition, the study offered an opportunity to introduce all dermatologists to this technique.